THEORETICAL FOUNDATIONS AND PEDAGOGICAL PRACTICES OF NATIONAL IDENTITY AFFIRMATION IN THE REPUBLIC OF POLAND - Svitlana Sysoievа (Неперервна професійна освіта: теорія та практика)
The article examines theoretical approaches and pedagogical practices for affirming national identity in the Republic of Poland in the context of the country’s membership in the European Union. The socio-political changes that began in the 1980s in Central and Eastern Europe led to identity becoming the subject of numerous discussions and a new challenge for individuals. Factors that initiated and sustained these discussions included the transformations in the countries of the former Soviet socialist bloc, related to systemic change, social transformation, and the emergence of non-governmental and civil society structures promoting a more unified European identity. Today, there are views on identity that differ from traditional perspectives, especially in the context of cultural diversity. Summarizing the positions of Polish scholars, the article concludes that identity is understood as a flexible and open category, dependent on the individual. Attention is drawn to a shift in understanding identity – not as something predetermined by socialization and education for life, but as a life project. These changes have been influenced by the openness of the European Union to new member states, freedom of movement within the EU, migration from third countries and the resulting diversity, as well as globalization processes. Intercultural education technologies are identified as effective pedagogical practices for affirming national identity. The Polish experience in exploring theoretical and pedagogical aspects of national identity affirmation leads to several conclusions: given Ukraine's Eurointegration aspirations, there is a need to intensify research on multidimensional identity formation, particularly its key components—national and European identity; intercultural education technologies should be widely implemented as a pedagogical practice fostering a culture of interaction with representatives of other cultures; the development of borderland pedagogy in Ukraine is advisable, aimed at affirming Ukrainian national identity in border regions through intercultural educational practices; there is an urgent need for interdisciplinary research on Ukraine’s borderlands to ensure national independence and unity. The uncompromising struggle of the Ukrainian nation has demonstrated to the world its desire for independence. The foundation of such unity and consolidation is a high level of self-awareness, civic responsibility, and Ukrainian national identity.